Distribution of Bivalve Abundance in the Intertidal Zone of Bandar Laksamana Sub-District, Bengkalis District, Riau Province - Muhammad Sabirin; Joko Samiaji; Efriyeldi Efriyeldi (Faculty of Fisheries and Marine, Universitas Riau, 2024)
This study was conducted in June 2022 to know the diversity and abundance of bivalve species as well as know the relationship between the total organic matter content of sediments and the abundance of bivalves found in the intertidal zone of coastal waters of Bandar Laksamana District. This research was conducted using the survey method, where each station consisted of 3 plots perpendicular to the coastline. Station 1 is in Tenggayun Village, Station 2 is in Api-Api Village, and Station 3 is in Parit Satu Api-Api Village. Observations and sampling were conducted directly in the field and then analyzed at the Marine Biology Laboratory, Department of Marine Science, Faculty of Fisheries and Marine, Universitas Riau. Based on the research results, it is known that the highest abundance of bivalves is found at Station 2, which is 2.07 ind/m2 with an organic content of 2.44%. At the same time, the lowest abundance of bivalves is found at station 1, which is 0.44 ind/m2 with an organic content of 0.91%. The bivalves found include Corbicula javanica, Anadara granosa, Solen sp, Pharella acutidens, and Anadara antiquata.